Defect charge states in Si doped hexagonal boron-nitride monolayer. (13th January 2016) - Mapasha, R E; Molepo, M P; Andrew, R C; Chetty, N
Abstract: We perform ab initio density functional theory calculations to investigate the energetics, electronic and magnetic properties of isolated stoichiometric and non-stoichiometric substitutional Si complexes in a hexagonal boron-nitride monolayer. The Si impurity atoms substituting the boron atom sites SiB giving non-stoichiometric complexes are found to be the most energetically favourable, and are half-metallic and order ferromagnetically in the neutral charge state. We find that the magnetic moments and magnetization energies increase monotonically when Si defects form a cluster. Partial density of states and standard Mulliken population analysis indicate that the half-metallic character and magnetic moments mainly arise from the Si 3 p impurity states. The stoichiometric Si complexes are energetically unfavorable and non-magnetic. When charging the energetically favourable non-stoichiometric Si complexes, we find that the formation energies strongly depend on the impurity charge states and Fermi level position. We also find that the magnetic moments and orderings are tunable by charge state modulation q   =  −2, −1, 0, +1, +2. The induced half-metallic character is lost (retained) when charging isolated (clustered) Si defect(s). This underlines the potential of a Si doped hexagonal boron-nitride monolayer for novel spin-based applications.